2010
DOI: 10.1590/s0103-84782010005000049
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric parameters comparisons of the digestive tract of four teleosts with different feeding habits

Abstract: Comparações de parâmetros morfométricos do trato digestório de quatro teleósteos com diferentes hábitos alimentares ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
7
0
7
Order By: Relevance
“…The frequency of items within a stomach may simply be a reflection of what is most available in the environment (Hershey, ; Becker et al , ). In all three species, the frequency of prey items within the stomach was not proportional to what was available in isolated pools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of items within a stomach may simply be a reflection of what is most available in the environment (Hershey, ; Becker et al , ). In all three species, the frequency of prey items within the stomach was not proportional to what was available in isolated pools.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that during isolation, fishes had a more specialized diet (Balcombe et al , ) and switched to nutritionally poorer, but available food resources (Kitchell & Windell, ; Closs & Lake, ), compared with when the stream is connected. In addition, fishes that digest less nutritional or less available food have been shown to increase gastrointestinal tract (GIT) length to increase nutrient absorption (Sibly, ; Zhixin e t al ., ; Becker et al , ). This concept has, however, only been tested within aquaculture and not in a natural habitat.…”
Section: Introductionmentioning
confidence: 99%
“…A mudança quantiqualitativa no componente principal na dieta e a variação do habitat podem resultar numa série de adaptações e/ou modificações do trato digestório, numa mesma espécie ou grupo de espécies, para explorar de forma eficaz o alimento. O sistema de criação e habitat dos peixes podem também interferir na morfologia do corpo e dos órgãos dos animais (BECKER et al, 2010).…”
Section: Introductionunclassified
“…Entre os teleósteos existem variações anatômicas e histológicas marcantes no trato gastrintestinal (TGI), que por suas intrigantes particularidades e importância para o crescimento do peixe, vem sendo alvo de estudos (ALBRECHT;CARAMASCHI, 2001;BECKER et al, 2010;RAŠKOVIĆ et al, 2011;RODRIGUES et al, 2009).…”
Section: Anatomia E Histologia Do Intestino De Peixesunclassified